Theoretical Study of Adsorption of Solriamfetol Drug on Surface of the B12N12 Fullerene: A DFT/TD-DFT Approach - Yahyaei, Hooriye; Sharifi, Shamsa; Shahab, Siyamak; Sheikhi, Masoome; Ahmadianarog, Mahin (Letters in Organic Chemistry, 2021)
For the first time in the present study, we studied the adsorption effect of the Solriamfetol (SOF) on the electronic and optical properties of B12N12 fullerene using density functional theory (DFT) and time-dependent density functional theory (TD-DFT) calculations with the M062X/6- 311++G(d,p) level of theory in the solvent water. The calculated adsorption energies of SOF drug with the B12N12 fullerene were computed at T= 298.15 K with the M062X functional. The UV/Vis absorption spectra were computed and investigated for the study of the significant changes in interactions between SOF and B12N12 fullerene. The IR spectra were also calculated and investigated. The calculated results indicate that the adsorption of the SOF drug from its internal NH2 group on the B12N12 fullerene (configuration B) has the most chemical stability rather than configuration A and C. According to the NBO results, the SOF molecule and B12N12 fullerene are identified as both electrons donor and acceptor at the complexes B12N12-SOF. On the other hand, the charge transfer occurs between the bonding, anti-bonding, or nonbonding orbitals in the SOF drug and B12N12 fullerene. It is found that the applied B12N12 fullerene can be suitable as a drug carrier for the delivery of SOF as a drug for the treatment of excessive sleepiness.
Keywords: B12N12 fullerene